Formation and growth mechanism of a manganese phosphate coating on an as-cast Zr–Al binary alloy. (4th March 2017) - Guo, D.; Zhang, Y.; Li, Q.; Xiao, F. R.; Mao, L.; Wang, B.
Abstract : The preparation of a manganese phosphate coating on an as-cast Zr–Al alloy is described. The alloy consisted of an α phase (α-Zr) and a β phase (Zr2 Al), where α-Zr is the matrix and Zr2 Al spreads along the grain boundaries discontinuously. The coating was divided by cracks to exhibit a network structure. The manganese phosphate coating showed a combination of crystalline and amorphous structure. The film consists of small particles densely packed. It is uniform and compact. The formation of the phosphate coating on substrates treated for short periods was investigated. Mn5 (PO4 )(OH)2 ·H2 O and MnZr(PO4 )2 ·4H2 O phases were found in the manganese phosphate coatings. The grain particles are preferentially deposited on the β phase rather than on the α phase.